Dual Collection Channels Under a Carbon Tax Scheme in CLSC: Decentralized vs. Alliance - Nur Layli Rachmawati; Chung-Chi Hsieh (Engineering Proceedings)
This paper compares dual collection mode strategies under carbon tax regulation: (1) a decentralized strategy when both manufacturer and retailer collect EoL independently and they determine their pricing and collection decision separately and (2) an alliance strategy by incorporating backward integration, when manufacturer and retailer make an alliance to recycle EoL but their pricing decisions are determined independently. The results show that the alliance strategy performs better in terms of total supply chain profit. Performing alliances benefits the manufacturer and supply chain.